2010
DOI: 10.1007/s11832-010-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

Failures and complications in intramedullary nailing of children's forearm fractures

Abstract: The analysis of the failures and complications shows that a differentiated approach to the data has to be taken. Most complications occur because of incorrect use of the method with neglect of biomechanical principles. The usage of the ESIN method is extended to more problematic regions, such as the distal diaphyseal portion of the forearm, and therefore, an increase in complications is likely. Despite this risk, ESIN should still be the standard treatment for forearm shaft fractures in children, and no change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 31 publications
3
90
0
6
Order By: Relevance
“…In addition, two articles were identified from citation list of selected articles. In total we could find 11 studies or case reports referring to refractures of the forearm with ESIN in situ, accounting for 0.8–8.6% (average 2.3%) of study population5 6 11–19 (table 1). This complication typically occurs after a second trauma more than a month after the initial fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two articles were identified from citation list of selected articles. In total we could find 11 studies or case reports referring to refractures of the forearm with ESIN in situ, accounting for 0.8–8.6% (average 2.3%) of study population5 6 11–19 (table 1). This complication typically occurs after a second trauma more than a month after the initial fracture.…”
Section: Discussionmentioning
confidence: 99%
“…2 Perfect anatomic reductions of these fractures are not necessary in children, as their immature bones have the ability to remodel which may correct any residual deformity. 3 It has been reported that angulation of approx 10 degrees in children is likely to remodel overtime. 3 Operative fixation is indicated in a minority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has been reported that angulation of approx 10 degrees in children is likely to remodel overtime. 3 Operative fixation is indicated in a minority of cases. This include fractures that are unstable, with an angulation of more than 10 degrees post closed reduction, displaced fracture of proximal third of radius, and in an open fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of this technique has been validated by many studies showing that the procedure is straightforward, reproducible, has good outcomes and few complications [6e8]. The most common reported complications after ESIN are by order of frequency refractures, lesion of the superficial radial nerve and delayed union [9]. With regards to the material used for ESIN, results are similar whether stainless steel Kirschner wires (K-wires) or titanium nails are used [10,11].…”
Section: Introductionmentioning
confidence: 99%